1952
DOI: 10.1161/01.cir.5.4.605
|View full text |Cite
|
Sign up to set email alerts
|

The Abnormal Serum Lipid Pattern in Patients with Coronary Arteriosclerosis

Abstract: Studies in experimental arteriosclerosis have indicated that the relative level of serum lipid phosphorus may be as significant a factor as the absolute level of serum cholesterol in the production of arterial lesions. For this reason, the serum lipid pattern of 82 patients with coronary arteriosclerosis has been compared with that of 112 healthy adults. An elevation of the serum cholesterol, serum lipid phosphorus and the serum cholesterol-lipid phosphorus molar ratio has been found in most of the patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1953
1953
1962
1962

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…(1950), Steiner et al (1952), and other smaller studies conducted in the United States are thus confirmed. An exception to this generalization has occurred in this study in the sixth decade in women and will be discussed later.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…(1950), Steiner et al (1952), and other smaller studies conducted in the United States are thus confirmed. An exception to this generalization has occurred in this study in the sixth decade in women and will be discussed later.…”
Section: Discussionsupporting
confidence: 63%
“…The lipid composition of atherosclerotic plaques and of plasma is similar enough to suggest that the lipids of the plaques may have their origin in the plasma (Weinhouse and Hirsch, 1940;Buck and Rossiter, 1951) and labelled cholesterol studies have shown that this plasma lipid is, in fact, incorporated into the atherosclerotic plaque (Biggs et al, 1952). Less comprehensive studies of the plasma lipids in normal subjects compared with patients with coronary artery disease have been made in the United States (Morrison et al, 1948;Gertler et al, 1950;Steiner et al, 1952). It was thought that a larger study, precisely controlled in respect of age and sex, would be of value especially if conducted in Britain where the dietary habits differ to some extent from those elsewhere.…”
mentioning
confidence: 99%
“…This observation lends support to the concept that the ratio of total cholesterol to lipid phosphorus is by far of greater importance than either serum total cholesterol or serum lipid phosphorus in assessing the genesis of atherosclerosis. 4' 7, 8 From Gofman's observations that the Sf [10][11][12][13][14][15][16][17][18][19][20] with atherosclerosis, the level of serum total cholesterol may be employed as a guide to the molecules do not change in men after the midthirties, but do continue to rise steadily ill women. Perhaps the female has additional protective mechanisms which, in spite of the high concentration of Sf 10-20 molecules in the serum, exert a salutary effect.…”
Section: Total Cholesterol-lipid Phosphorusmentioning
confidence: 99%
“…There is wide division of opinion as to the significance of stress. There may even be several groups of individuals prone to coronary disease' [1][2][3][4][5][6][7][8][9][10][11][12][13] the inyocardial lesions. Until more is learned about the effect of hypotension, fever, tissue necrosis, etc., during the acute episode, it will be difficult to determine which of these changes might be associated with the lipid changes occurring immediately after infarction.…”
mentioning
confidence: 99%
“…Such factors do not enter into the evaluation of the men. In the men the 'e was a definite tendency for the -S [1][2][3][4][5][6][7][8][9][10] concentration to be decreased, although 6 of 22 patients studied 3 months to 10 years after occurrence of infarction had normal values.…”
mentioning
confidence: 99%